Government support for addressing energy poverty in the context of low-carbon transition - Svitlana Naumenkova; Svitlana Mishchenko; Ievgen Tishchenko; Volodymyr Mishchenko (Public and Municipal Finance)
The development and implementation of state policy to overcome energy poverty has become particularly important in Ukraine and requires adequate methods and tools to support consumers in transitioning to a low-carbon economy. The study aims to conduct a comparative analysis of energy poverty in the EU and Ukraine, evaluate the cost of government support for vulnerable households through subsidy mechanisms, and improve the methodology for calculating heating subsidies in Ukraine under low-carbon transition conditions. Based on statistical data, the study reveals the intensifying negative impact of the 2021–2022 energy crisis on households in both the European Union and Ukraine. The results of evaluating the cost and structure of energy subsidy portfolios indicate that most governments worldwide are shifting toward economic decarburization and phasing out coal consumption subsidies in response to stricter climate obligations. The findings reveal that while energy subsidies in Ukraine are socially oriented, they place a significant burden on the state budget and fail to address the root causes of energy poverty. The paper explores the mechanism of fuel subsidies and argues that the implementation of energy efficiency measures must accompany the gradual elimination of such support. It also presents a calculation of heating subsidies based on the energy efficiency class of residential buildings, consistent with the goal of introducing NZEB standards. The formulated proposals seek to strengthen support for energy-vulnerable households and enhance monitoring activities to obtain more comprehensive and objective data on the extent of energy poverty in Ukraine.